2016
DOI: 10.1080/02786826.2016.1143084
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of jet-induced resuspension of indoor deposited particles

Abstract: Particles deposited on indoor surfaces may be resuspended and become airborne when disturbed by intensive jets. Depending on the intended purpose, the resuspension of deposited particles may be minimized or promoted. This investigation experimentally measured the resuspension of Arizona test dusts (ATDs) after a jet impingement. The simulating pulsed jets were created by a tube using compressed nitrogen gas. The jets were released into the test section in a wind tunnel that was cleaned by high-efficiency parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The results shown in Figure 2 demonstrate that the highest reaerosolization was at a location »1 mm from the center of the jet (maximum peak location). Mei et al (2016) also showed a region of high particle reaerosolization away from the center. In our results, reaerosolization increased with particle size; resuspension of 5 mm particles reached »90% at the peak location.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results shown in Figure 2 demonstrate that the highest reaerosolization was at a location »1 mm from the center of the jet (maximum peak location). Mei et al (2016) also showed a region of high particle reaerosolization away from the center. In our results, reaerosolization increased with particle size; resuspension of 5 mm particles reached »90% at the peak location.…”
Section: Resultsmentioning
confidence: 96%
“…Other studies have evaluated the effect of distance between the surface and the orifice on reaerosolization. A study by Mei et al (2016) showed that there may be an optimal jet impingement height for high surface dust load conditions; for low dust conditions, they did not observe an optimum height, but they did observe more reaerosolization as the separation distance was reduced.…”
Section: Methodsmentioning
confidence: 99%
“…The solar radiation reaching on to the device surfaces is immensely affected by the accumulated dust layer 1 , which is more pronounced in nearby desert environments where the frequent dust storms occur. Some cleaning techniques were used for dust mitigation, such as brushing 2 , electrostatic repelling 3 , 4 , water spreading 5 , air puffing 6 , liquid droplet rolling 7 , mechanical vibration 8 , ultrasonic cleaning 9 , etc. These techniques are effective in dust mitigation from surfaces even though they have some shortcomings in terms of high energy consumptions, scarcity of clean water, and expensive air compression.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have evaluated the contribution of surface properties to reaerosolization (Goldasteh et al 2012;Mei et al 2016). Adhesive and removal forces depend on particle diameter, with larger particles having more adhesive force with the surface compared to smaller particles; however, larger particles stick up higher into the viscous sublayer of the boundary layer and thus experience higher removal forces (Loosmore 2003).…”
Section: Introductionmentioning
confidence: 99%